2021
DOI: 10.1038/s41598-021-03346-0
|View full text |Cite
|
Sign up to set email alerts
|

The activation fragment of PAR2 is elevated in serum from patients with rheumatoid arthritis and reduced in response to anti-IL6R treatment

Abstract: Osteoarthritis (OA) and rheumatoid arthritis (RA) are serious and painful diseases. Protease-activated receptor 2 (PAR2) is involved in the pathology of both OA and RA including roles in synovial hyperplasia, cartilage destruction, osteophyogenesis and pain. PAR2 is activated via cleavage of its N-terminus by serine proteases. In this study a competitive ELISA assay was developed targeting the 36-amino acid peptide that is cleaved and released after PAR2 activation (PRO-PAR2). Technical assay parameters includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Closely monitoring PAR2-peptide levels in a patient before and after surgery might thus allow the detection of regrowing tumors, if they become inflamed. PAR2 expression is not specific to GBM and fragments have been detected in other diseases 80 . Despite a much higher peptide coverage, we did not identify any circulating PAR2 peptides in the Meningioma control cohort.…”
Section: Par2 Abundance In Highly Individual Serum Proteomes Matches ...mentioning
confidence: 99%
“…Closely monitoring PAR2-peptide levels in a patient before and after surgery might thus allow the detection of regrowing tumors, if they become inflamed. PAR2 expression is not specific to GBM and fragments have been detected in other diseases 80 . Despite a much higher peptide coverage, we did not identify any circulating PAR2 peptides in the Meningioma control cohort.…”
Section: Par2 Abundance In Highly Individual Serum Proteomes Matches ...mentioning
confidence: 99%
“…its pro-inflammatory effects, PAR-2 has also been shown to play a role in pain regulation in OA [69]. Activation of PAR-2 in sensory nerve endings has been shown to lead to the release of pain-causing substances, such as substance P and calcitonin gene-related peptide (CGRP), which can contribute to the development of joint pain in OA.…”
Section: Plos Onementioning
confidence: 99%
“…Being able to evaluate the activation state of the receptor, instead of its presence on the cell surface, may be a more accurate approach to evaluate the activity of this inflammatory pathway and may also function as a biomarker that could be used in asthma. A recent study showed that the small peptide liberated from the receptor when it is cleaved by activating serine proteases can be detected in human serum and its levels increase in patients with rheumatoid arthritis and responds to treatment of the disease with specific biologics (109). It will be interesting to test whether the levels of this peptide also change in asthma and whether it may be used as another biomarker for asthma severity and/or control.…”
Section: Par 2 Expression As An Asthma Biomarkermentioning
confidence: 99%